Health care providers' decision-making and early adoption of tenofovir alafenamide for HIV preexposure prophylaxis: An inductive qualitative study. - Elisabeth Merchant; Patricia Solleveld; Kevin Gibas; Douglas Krakower (PLoS ONE, 2024)
Background Over the past several years, there have been several changes affecting the available options for oral HIV preexposure prophylaxis, including approvals for tenofovir alafenamide with emtricitabine in 2019 and a generic formulation of tenofovir disoproxil fumarate with emtricitabine in 2020. Methods In order to better understand providers' decision-making processes when deciding between these two drugs for pre-exposure prophylaxis, we conducted semi-structured in-depth interviews with resident, fellow and attending physicians in internal medicine and infectious diseases between May 2020 and March 2021. These interviews were analyzed to identify emergent codes, which were utilized in an inductive thematic analysis to identify major themes pertinent to pre-exposure prophylaxis decision-making. Results Of 21 participants, 18 expressed a general preference for prescribing tenofovir disoproxil fumarate with emtricitabine, 2 preferred tenofovir alafenamide with emtricitabine and 1 had no specific preference. Providers perceived similar efficacy of the two formulations, and their clinical decisions were influenced primarily by whether HIV pre-exposure prophylaxis users belonged to a population with an indication for each of the two drugs (e.g. gender-related restrictions for tenofovir alafenamide), the medications' differing side effect profiles, cost and insurance considerations, prior personal and collective experience with each of these medications, and personal preferences. Respondents also noted that both providers and HIV pre-exposure prophylaxis users were influenced by external factors, including institutional prescribing guidance, advertising, and social influences, including from peers and colleagues. Conclusions Our findings suggest that unbiased educational campaigns for both prescribers and users of HIV pre-exposure prophylaxis will be important to support evidence-based prescribing practices and cost-effective decisions among oral pre-exposure prophylaxis options.